2017
DOI: 10.1002/pssb.201600713
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of bulk GaN grown by HVPE: Effect of Si doping

Abstract: The thermal conductivity of bulk GaN grown by Hydride Phase Vapor Epitaxy with intentional Si doping was measured using the 3ω method. The effect of Si concentration ranging from 1.6 × 1016 to 7 × 1018 cm−3 on the thermal conductivity was studied over the temperature range of 295–470 K. The room temperature thermal conductivity was found to decrease with increasing Si doping from 245 to 210 W/m · K. Also, for each Si doped sample the thermal conductivity decreases with increasing temperature. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Even though the thermal conductivity of bulk and film GaN was extensively investigated over the last decades [12][13][14][15][16][17][18], there were only several reports on thermal conductivity of AlGaN films and AlN/GaN superlattices. Results of the measurements of Al x Ga 1−x N films (with x changing from 0.1 to 0.44) showed that thermal conductivity decreases with increasing amount of Al mass fraction and decreasing film thickness [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the thermal conductivity of bulk and film GaN was extensively investigated over the last decades [12][13][14][15][16][17][18], there were only several reports on thermal conductivity of AlGaN films and AlN/GaN superlattices. Results of the measurements of Al x Ga 1−x N films (with x changing from 0.1 to 0.44) showed that thermal conductivity decreases with increasing amount of Al mass fraction and decreasing film thickness [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, existing experimental measurements of the phonon dispersion relation of -GaN are limited to ambient conditions, and the phonon scattering processes and the temperature effects are mostly unexplored [9,10]. Moreover, the anisotropic thermal transport of -GaN along a (inplane) and c (out-of-plane) axis directions remains controversial due to the challenges in transport measurements [7,[11][12][13][14][15][16][17][18] and calculations [19][20][21]. Therefore, a more comprehensive understanding of the phonon dynamics is pivotal to investigating the thermal transport and other thermodynamics properties of GaN.…”
mentioning
confidence: 99%
“…For GaN doped with Si, phonon scattering by free electrons should be further considered and can reduce the room-temperature thermal conductivity by ~13% at a doping level of 7.0×10 18 cm -3 . 16 This new phonon-scattering mechanism is further considered for heavily doped GaN nanowires and the scattering rate is given as 12 ( ) 2 *3 1 4 * 2 * 2 2 2 * 2 * 2 2 2 * 2 1 4 2…”
mentioning
confidence: 99%